Evaluation on strength of chemically treated 2 and 4 years old Bamboo Bambusa vulganis through pressurized treatment - Razak Wahab; Mohammed Abdus Salam; Aminuddin Mohamed; Hashim W. Samsi; Shafiqur Rahman; Mohd Sukhairi Mat Rasat; Izyan Khalid (RJPBCS, 2015)
Evaluation on the strengths of chemically treated 2 and 4 year-old bamboo Bambusa vulgaris through pressurized process were conducted. The preservatives used in this study were the ammonium-copper-quaternary, copper-chrome-arsenic and mixture of borax-boric acid. The level of chemicals concentrations used were at 2% and 4% respectively. An overall strength reduction occurred after undergoing the treatment process. The strength reduction ranged from 4.9 to 7.6% for ACQ, 5.0 to 7.2% for BBA and 5.9 to 7.9% for CCA treated bamboo. The reductions in the strengths were found to be dependent on the type of preservatives applied, concentration used and their retention in the treated bamboo